Tau, atrophy, and domain-specific cognitive impairment in typical Alzheimer's disease - Wuestefeld, Anika ; 0000-0003-1779-3388; Xie, Long; McGrew, Emily; Pichet-Binette, Alexa; Spotorno, Nicola; van Westen, Danielle ; 0000-0001-8649-9874; Mattsson-Carlgren, Niklas ; 0000-0002-8885-7724; Yushkevich, Paul A; Das, Sandhitsu R; Wolk, David A; Wisse, Laura E M ; 0000-0001-7504-3943 (Alzheimer's & dementia : the journal of the Alzheimer's Association, 2025)
INTRODUCTION: A granular understanding of the mechanisms linking tau pathology to cognitive decline in Alzheimer's disease is crucial. We investigate mediating effects of medial temporal lobe (MTL) and neocortical neurodegeneration on tau-induced domain-specific cognitive impairment in amyloid-beta (Aβ) positive cognitively normal and impaired adults. METHODS: We assessed magnetic resonance imaging-derived MTL and neocortical volume/thickness and 18F-Flortaucipir positron emission tomography in 319 Aβ-positive individuals. Cognitive functions across six domains were isolated by adjusting for other cognitive measures. RESULTS: MTL tau correlated with memory subdomains, neocortical tau with executive function, and both with semantic fluency. Specific structural measures partially mediated these tau-cognition associations: Brodmann area 35 mediated tau-immediate and tau-delayed recall, posterior hippocampus tau-recognition, and inferior temporal cortex tau-semantic fluency associations. DISCUSSION: Our findings provide a nuanced understanding of region-specific macrostructural atrophy as one pathway of tau-induced cognitive changes, aligning with known tau spread patterns. Additionally, isolating cognitive functions is a promising approach for future research. HIGHLIGHTS: Medial temporal lobe tau was related to memory domains; neocortical tau to executive function. Both tau positron emission tomography measures were associated with semantic fluency. Specific regional atrophy partially mediated tau-induced cognitive changes. Other mechanistic links between tau and cognitive subdomains require investigation. Isolated cognitive domains should be explored as future avenues of research.
© 2025 The Author(s). Alzheimer's & Dementia published by Wiley Periodicals LLC on behalf of Alzheimer's Association.
Keywords: Humans; Alzheimer Disease/pathology; Male; Female; tau Proteins/metabolism; Atrophy/pathology; Positron-Emission Tomography; Cognitive Dysfunction/pathology; Magnetic Resonance Imaging; Aged; Temporal Lobe/pathology; Neuropsychological Tests; Middle Aged; Amyloid beta-Peptides/metabolism; Neocortex/pathology